2014
DOI: 10.1249/mss.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Capacity and Cognitive Control in Elementary School-Age Children

Abstract: Purpose The current study examined the relationship between children’s performance on the Progressive Aerobic Cardiovascular Endurance Run (PACER) subtest of the FitnessGram® and aspects of cognitive control that are believed to support academic success. Methods Hierarchical linear regression analyses were conducted on a sample of 2nd and 3rd grade children (n = 397) who completed modified versions of a flanker task and spatial n-back task to assess inhibitory control and working memory, respectively. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
4
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 35 publications
11
96
4
4
Order By: Relevance
“…The sample size in these studies has ranged from 24 to 224 children among the ages of 6 and 13 years old (with a mean age of 9 or 10 in 75% of the studies). Fitness has most often been measured using a shuttle-run task (often the PACER) (7, 16, 82, 83, 91, 140, 141) or a graded exercise test (24-27, 29, 50, 60, 96, 129-131, 161, 167). In addition to the large number of studies assessing fitness, there is one study that assessed PA objectively using accelerometry (148) and one study that assessed sport participation in addition to their measure of fitness (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size in these studies has ranged from 24 to 224 children among the ages of 6 and 13 years old (with a mean age of 9 or 10 in 75% of the studies). Fitness has most often been measured using a shuttle-run task (often the PACER) (7, 16, 82, 83, 91, 140, 141) or a graded exercise test (24-27, 29, 50, 60, 96, 129-131, 161, 167). In addition to the large number of studies assessing fitness, there is one study that assessed PA objectively using accelerometry (148) and one study that assessed sport participation in addition to their measure of fitness (7).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the large number of studies assessing fitness, there is one study that assessed PA objectively using accelerometry (148) and one study that assessed sport participation in addition to their measure of fitness (7). With regard to the statistical analyses, fitness or activity has either been maintained as a continuous variable (7, 16, 50, 60, 91, 96, 118, 140, 141, 148), has been used to categorize participants as low- or high-fit, with this judgment typically based upon normative PACER data (82, 83) or normative VO 2max data (24-27, 29, 129-131, 161, 167), or participants have been identified as athletes or non-athletes (7). When researchers have categorized participants as low- or high-fit, the average difference in VO 2max among the groups is 14.75 ml/kg/min (SD=4.76, n=13) and the average difference in the number of laps in a shuttle run task is 18.40 laps (SD=0.28, n=2), indicating that there are substantial fitness differences among the groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other outcomes besides metabolic syndrome should be evaluated because physical fitness is associated with more than just cardiometabolic risk. For example, recent research has shown the HFZ to be related to risk for depression (Rieck, Jackson, Martin, Petrie, & Greenleaf, 2013), blood markers of nonalcoholic fatty liver disease (Trilk et al, 2013), academic achievement (Wittberg, Northrup, & Cottrell, 2012), and cognitive control (Scudder et al, 2014).…”
Section: S17mentioning
confidence: 99%
“…Although the effects of specific sports activities on executive functions are still uncertain (Ishihara, Sugasawa, Matsuda, & Mizuno, 2016), many cross-sectional and longitudinal intervention studies have shown a relationship between a sports activity and cognitive function (Alesi, Bianco, Luppine, Palma, & Pepi, 2016;Davis et al, 2007;Huijgen et al, 2015;Ishihara, Sugasawa, Matsuda, & Mizuno, 2017;Lundgren, Högman, Näslund, & Parling, 2016;Scudder et al, 2014;Vestberg et al, 2012). From the point of view of the level of sports activity, Heppe, Kohler, Fleddermann, and Zentgraf (2016) found that elite athletes (playing different team sports), performed better in sustained attention tests, compared to recreational athletes.…”
Section: Introductionmentioning
confidence: 99%